1990
DOI: 10.3109/02656739009140827
|View full text |Cite
|
Sign up to set email alerts
|

A DNA double-strand break repair-deficient mutant of CHO cells shows reduced radiosensitization after exposure to hyperthermic temperatures in the plateau phase of growth

Abstract: Heat response and heat-induced radiosensitization were studied in plateau-phase cultures of CHO cells and their radiation-sensitive counterpart, the xrs-5 cells. The xrs-5 cells were more sensitive to heat alone than were CHO cells. A large enhancement in radiation-induced killing was observed in CHO cells pre-exposed to heat (43 degrees C), expressed as a reduction in the values of Do and Dq. Contrary to the results obtained with CHO cells, pre-exposure to heat of xrs-5 cells affected radiation sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…However, a di erent cell line and di erent temperatures were used than in the study by Wong et al (1995), and thus the results may not be directly comparable. In general these studies agree with and support the earlier ® ndings that hyperthermia can reduce the repair of radiation induced dsb's, even though in many of those experiments the DNA break studies were done at much higher doses than the survival studies (Corry et al 1977, Mills and Meyn 1981, Dikomey 1982, Jorritsma and Konings 1983, Radford 1983, 1986, Warters et al 1987, Raaphorst 1989, Iliakis and Seaner 1990, Dikomey and Franzke 1992, Warters and Axtell 1992, Warters 1993, Nevaldine et al 1994, Wong et al 1995, DahmDaphi et al 1997. Thus the studies of comparing survival and dsb production and repair at equal doses help validate the earlier studies, in which the dsb experiments tended to have much higher doses than the survival experiments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, a di erent cell line and di erent temperatures were used than in the study by Wong et al (1995), and thus the results may not be directly comparable. In general these studies agree with and support the earlier ® ndings that hyperthermia can reduce the repair of radiation induced dsb's, even though in many of those experiments the DNA break studies were done at much higher doses than the survival studies (Corry et al 1977, Mills and Meyn 1981, Dikomey 1982, Jorritsma and Konings 1983, Radford 1983, 1986, Warters et al 1987, Raaphorst 1989, Iliakis and Seaner 1990, Dikomey and Franzke 1992, Warters and Axtell 1992, Warters 1993, Nevaldine et al 1994, Wong et al 1995, DahmDaphi et al 1997. Thus the studies of comparing survival and dsb production and repair at equal doses help validate the earlier studies, in which the dsb experiments tended to have much higher doses than the survival experiments.…”
Section: Discussionsupporting
confidence: 80%
“…However, in order to assess the damage at the same dose range as used in survival, many investigators evaluated the e ects on DNA single stranded breaks (ssb), which do not correlate well with survival (Corry et al 1977, Clark et al 1981, Mills and Meyn 1981, Jorritsma and Konings 1983, Warters et al 1987, Dikomey and Franzke 1992, or others have attempted to measure survival at low doses whilst measuring DNA double stranded breaks (dsbs) at very high doses (Dikomey 1982, Radford 1983, Iliakis and Seaner 1990, Warters and Axtell 1992. Most of these studies showed that hyperthermia had a inhibitory e ect on DNA strand break repair and support the concept that its radiosensitizing e ect is through the inhibition of repair of DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Our results do not prove that degradation of BRCA2 is the sole or even most important effect of heat on DNA repair or on other cellular processes relevant for cell killing. In fact, multiple hyperthermia targets have been described (29)(30)(31)(32)(33)(34). They do demonstrate, however, that hyperthermia can be a powerful, noninvasive tool to locally introduce BRCA2 degradation and HR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some cell lines deficient in Ku protein or DNA-PKcs do not show thermal radiosensitization (i.e. their intrinsically high sensitivity to radiation is not further increased by heat) (21,22). This implicates DNA-PK in the thermal radiosensitization phenomenon.…”
mentioning
confidence: 99%